PINJAMAN ONLINE DALAM TINJAUAN HUKUM ISLAM - Thoha, Aris Badaruddin (LPPM STMIK El Rahma Yogyakarta, 2022)
The development of information and communication technology has an impact on the emergence of new innovations in various fields of human life. One of these innovations is in the field of financial technology (fintech), one of which is electronic-based money lending transactions which became popular with the term online loans (Pinjol). Pinjol has become a business trend and has become the choice of many people because it is considered to promise convenience, is seen as more effective, fast and easy than having to meet in person at the location to carry out debt transactions. However, borrowing transactions in practice leave many problems in society such as loan interest that strangles borrowers, physical threats to borrowers who cannot pay debts or installments, digital terror and threats to spread private secrets to the public through social media and so on. This study will answer how the views of Islamic law are related to loan transactions. The type of research used is library research with a normative qualitative approach by collecting information and OJK data about online loans and DSN MUI fatwa documents. The analysis was carried out using a qualitative method, namely explaining and describing the data obtained from the research and grouped according to their quality and truth to answer the problem. The results of this study are that online loan transactions are legal and permissible as long as they are in accordance with sharia principles. The implementation of online loan services must not conflict with sharia principles, including avoiding usury, gharar, maysir, tadlis, dharar, zhulm, and haram.